A NEW ‘RAY OF LIGHT’ IN SOCIO-ECONOMIC RIGHTS JURISPRUDENCE? A NOTE ON COUGHLAN NO V ROAD ACCIDENT FUND (CENTRE FOR CHILD LAW AMICUS CURIAE) (CCT160/14) [2015] ZACC 9 (The Pretoria Student Law Review, 2021)
The justiciability of socio-economic rights in the South African courts has been the subject of much academic debate. This issue of justiciability spans back to the drafting of the final Constitution — the question at the time concerned whether or not these rights should be included in Chapter II of the Constitution. The fact that the justiciability of socio-economic rights has been an on-going concern for the last two decades illuminates the difficulties faced by the courts in giving substantive content to these rights. The courts often respond to these situations by way of deference.1 Brand defines deference as ‘a strategy of the courts, when faced with difficult, technical or contested social questions…to leave the decision of those issues in different ways and to varying degrees, to the other branches of government.’2 The judgment of Coughlan NO v Road Accident Fund (Centre for Child Law Amicus Curiae) (CCT160/14) [2015] ZACC 9 is arguably described as a ray of light amongst the dark clouds that normally shroud socio-economic rights jurisprudence.
Keywords: socio-economic rights; South African courts; justiciability